A new autologous block-bone prefabricated flap concept based on the supraclavicular artery island flap (SCAIF) for reconstruction of a neo-mandibular osteoradionecrosis (ORN) defect, IDEAL Stage 1 report. (June 2017) - Douglas, Andrew J.W.; Kyzas, Panayiotis A.
Abstract: Reconstruction of the mandible due to osteoradionecrosis (ORN) can be very challenging. Currently, only complex high-risk options are available, and microvascular free-tissue transfer of composite flaps is considered the gold standard. However, this is fraught with an increased risk of perioperative complications. This technical note presents, for the first time, an IDEAL Stage 1 use of a prefabricated supraclavicular artery island flap (SCAIF) for the reconstruction of an ipsilateral mandibular defect, on a patient with advanced mandibular ORN. We have used an iliac crest cancellous bone block. This was shaped into the anticipated defect and was allowed additional length. It was then inserted into a fasciocutaneous pocket within the region planned for harvest as the skin paddle of the SCAIF. The bone was left in-situ for approximately seven weeks to achieve blood supply. The SCAIF flap was raised as a composite flap. Excellent integration and bleeding from the bone was clearly evident. The cutaneous part of the flap was used to reconstruct the soft tissue defect and the bone was used to bridge the bone defect. We believe that this technique can be an excellent alternative option for reconstructing mandibular defects. It is simple, elegant, carries minimal morbidity, achieves equal or potentially better result than traditional microvascular free flaps and minimises hospital stay as compared to similar cases treated within the same department in a more conventional surgical manner. The long-term results of this technique are yet to be seen, however will form part of our IDEAL Stage 2a & 2b report. In the future, this may become the gold standard for ORN mandibular reconstruction.